Belohrbti detel Dendrocoos leucotos - Krofel, Miha (Acrocephalus, 2020)
One male observed feeding on a Black Locust Robinia pseudoacacia near Zabiče (UTM VL54, Southern Slovenia) on 23 Jul 2020; with 490 m a., this is one of the lowest records for the species in Slovenia
Keywords: belohrbti detel; Dendrocopos leucotos; ornitologija; ptice